2019
DOI: 10.1016/j.devcel.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Notch Triggers Neoplastic Tumorigenesis in a Transition-Zone-like Tissue Microenvironment

Abstract: Highlights d The Drosophila posterior salivary gland imaginal ring is a transition-zone model d Persistent Notch signaling induces neoplastic transformation in the transition zone d Endogenous inflammatory JAK-STAT and JNK signaling promotes tumorigenesis d JNK-induced MMP1 shapes a weaker ECM structure for advanced tumorigenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…The Notch signaling pathway is well known for its complexity. Its role in cancer has been extensively studied in the context of oncogenic Notch mutations (28,29). A previous study established a role for Notch in inhibiting osteoblast differentiation, and showed that its activation in committed osteosarcoma cells induces a highly tumorigenic phenotype (13).…”
Section: Discussionmentioning
confidence: 99%
“…The Notch signaling pathway is well known for its complexity. Its role in cancer has been extensively studied in the context of oncogenic Notch mutations (28,29). A previous study established a role for Notch in inhibiting osteoblast differentiation, and showed that its activation in committed osteosarcoma cells induces a highly tumorigenic phenotype (13).…”
Section: Discussionmentioning
confidence: 99%
“…(6) Jun N-terminal kinase signalling can be important in tumourigenesis at transition zones -where different epithelial cell populations meet, which are often hotspots for tumourigenesis (reviewed in Tamori and Deng, 2017). One such zone occurs in the Drosophila larvae at a site where polyploid salivary gland cells meet the diploid imaginal ring cells, where tumourigenesis occurs after transient whole animal N ACT expression due to upregulation of TNF-JNK and Jak-STAT signalling (Yang et al, 2019). (7) Overexpression of Canoe (Cno, an adherens junction scaffold protein) in the patched (ptc) expression domain in wing imaginal discs conversely promotes both overproliferation and ectopic cell death, as well as cell migration/invasion .…”
Section: Pro-tumourigenic Jnk Signallingmentioning
confidence: 99%
“…There are now many animal models for studying cancer, each with advantages and disadvantages (see Table 4). 215‐227 Despite caveats, model organisms (and, in many cases, the simple ones) 222,228,229 have been instrumental in the discovery of fundamental biological mechanisms relating to development, differentiation, cell growth, and cell death—all processes highly relevant to the biology of human cancers. Models in lower eukaryotes (flies, frogs, worms, and fish) are far less expensive to maintain than mammalian models (eg, mouse), their development time is relatively short, and their genomes are far simpler.…”
Section: Cancer Modelingmentioning
confidence: 99%